Digital Business Transformation: Marketing Strategy Of Tiktok App In Islamic Perspective - Cindy Ariza Hasibuan (Utami Publisher, 2025)
Humans act as khalifah of Allah Swt on this earth to organise and maintain the earth as well as possible as God created this universe. Thus humans must be able to embrace with balance the development of the world from era to era, such as the development of science and technology in this era of globalisation. Thus the purpose of this writing is to convey information to the general public about the development of digital business facilities that make it easier to achieve a desired thing, especially in knowing how marketing strategies in TikTok e-commerce activities as a means of promoting products or services based on Islam. By utilising the National Library of Indonesia website and Google Scholars search engine for library research is the method of this research. The results of this study tell us about the TikTok application besides being able to be used as social media in everyday life, TikTok also provides additional features to make money by trading in the application using various marketing strategies based on Islamic sharia.